Systems thinking: A review of sustainability management research. (1st April 2017) - Williams, Amanda; Kennedy, Steve; Philipp, Felix; Whiteman, Gail
Abstract: Scholars from a wide range of disciplines and perspectives have sought to unravel the high complexities of sustainability. A mature understanding of sustainability management requires studies to adopt a multidisciplinary systemic lens capable of appreciating the interconnectivity of economic, political, social and ecological issues across temporal and spatial dimensions. Yet the field of systems thinking in the context of sustainability management research is disparate and can benefit from a comprehensive review in order to assimilate the current fragmented body of research and to identify promising research directions. To address this gap, we conducted a review of the systems thinking and sustainability management literature from 1990 up to 2015 including 96 articles. In this review, we first present descriptives that show an emerging body of work rapidly growing since 2011. We found that 54 percent of articles were published in two transdisciplinary journals, demonstrating that a systemic approach is not yet prevalent in mainstream management journals. Second, we identify and describe the core theoretical concepts of systems thinking found in the literature including interconnections, feedbacks, adaptive capacity, emergence and self-organization. Third, findings show a number of research themes, including behavioral change, leadership, innovation, industrial ecology, social-ecological systems, transitions management, paradigm shifts and sustainability education. Finally we offer a cross-scale integrated framework of our findings, and conclude by identifying a number of promising research opportunities. Highlights: Research on systems thinking and sustainability management is synthesized. Number of articles published per year is found to be increasing. Core theoretical concepts and research themes are discussed. Conceptual basis for future research agenda using systems thinking is proposed.